Implementation of Student Worksheet Oriented to Critical Thinking Skills on Heat Transfer Material - Permana, Sutisna; Sopandi, Wahyu; Sujana, Atep; Widodo, Ari (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This research was initiated by the absence of students critical thinking skills in science learning which can be seen in filling out the Student Worksheet when doing practical activities. This study aimed to determine: 1) the implementation of POE-based Student Worksheet and 2) the results of POE-based Student Worksheet implementation in generating critical thinking skills for fifth grade students of Public Elementary School of Girimukti, Cijambe District, Subang Regency on heat transfer material. This research used descriptive qualitative method. The instruments used were observation sheets and test questions. Data were collected by filling out observation sheets and test questions. The data were analyzed by using qualitative descriptive, namely through scoring, percentage, interpretation, and a description of each aspect. The results of this study were namely: 1) The implementation of POE-based Student Worksheet in practical activities is in the